2018
DOI: 10.1155/2018/6371582
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Stingless Bee Honey from Heterotrigona itama Improves Antiobesity Parameters in High‐Fat Diet Induced Obese Rat Model

Abstract: Heterotrigona itama is a common stingless bee species found in Southeast Asia. Studies on the health benefits of its honey are limited in comparison with other stingless bee species. This study examines the antiobesity benefits found in stingless bee honey (SBH) from H. itama. The parameters used to measure the benefits were weight change, morphological structures, and biochemical characteristics. The research was conducted by using rats that were given a high-fat diet (HFD). In total 48 male Sprague Dawley (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
5
21
0
Order By: Relevance
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were demonstrated by Rafie and colleagues using stingless bee honey (SBH) from Heterotrigona itama . The rats showed reduced BMI, percentage body weight gain, adiposity index, and relative liver weight after a 6-week honey supplementation (500–1000 mg/kg) [ 85 ]. Ramli and colleagues also observed a reduction in body fat and omental fat mass in rats supplemented with 1 g/kg/day of Kelulut honey for 8 weeks [ 86 ].…”
Section: The Mechanisms Of Honey In Reversing Metabolic Changesmentioning
confidence: 99%
“…In a study conducted on obese rats treated with SBH, a significant reduction was observed in body mass index (BMI), percentage of body weight gain, adiposity index, relative organ weight (ROW), liver enzymes, triglycerides and low-density lipoprotein (LDL), while the level of high-density lipoprotein (HDL) was significantly increased [ 34 ]. SBH treatment showed a reduced number of adipocyte cells, while the hepatocytes found in the liver were less prone to rupturing when treated with SBH, suggesting that SBH improved the indicators associated with obesity reduction and reduced the health risks related to obesity [ 34 ]. Another study on diabetic rats showed that SBH kept fasting blood glucose, total cholesterols, triglyceride and LDL cholesterol at low levels, whereas serum insulin and HDL cholesterol levels were increased [ 38 ].…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…In addition, some inflammatory markers, such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), inhibitor of nuclear factor kappa-B kinase subunit beta (IKK-β), tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) and apoptosis marker caspase-9 showed a steady decrease following treatment with SBH, while anti-oxidative enzyme catalase was increased [ 38 ]. Together, these studies have shown that not only the antidiabetic properties of SBH as a protection agent against pancreas dysfunction, it also highlighted the potential anti-obesity activity of SBH, by maintaining the lipid profile in homeostasis and could even affect the morphological structures in the liver [ 34 , 38 ].…”
Section: Stingless Bee Honeymentioning
confidence: 99%